AKTIVISME DAN PERILAKU POLITIK ISLAM : Teori, Pemikiran dan Gerakan - Karim, Syahrir; Mamat, Samsu Adabi (Jurnal Diskursus Islam, 2013)
Secara umum bahwa pola dasar yang dihadapi politik Islam dalam hubungannya dengan negara adalah adanya kesulitan untuk membangun sintesis yang memungkinkan di antara keduanya. Faktor utama yang menyebabkan kemandegan politik ini adalah keinginan para pemikir dan aktivis politik Islam untuk membangun hubungan Islam dan Negara secara legalistik dan formalistik. Proses politik dan aktivisme Islam dari beberapa gerakan yang ada khususnya pasca reformasi telah memberikan warna tersendiri terhadap perpolitikan di Indonesia.ABSTRACTIslam at most cases is frequently considered more than a religion per se. This is reinforced by the emergence of different schools of jurisprudence, theology, and Islamic philosophy, which indicates the multi-interpretative Islamic teachings. This multi-interpretative character of Islam has served as the basis of Islamic elasticity within its long history. Furthermore, this character also indicates the presence of pluralism in Islamic tradition. This has always been a challenge as well as surging classic debate in Islamic activism and in developing future democratization. Islam as Muslims believe has shaped Islamic movements in their national and democratic life. The core of such a view lies deep inside human consciousness that religion should actually work within the very human life instead of being formally acknowledged to rule the life of human beings as certain nation citizens.